Estudio de factibilidad para la creación de una microempresa dedicada a la producción y comercialización de productos elaborados a base de chocho. - Pinanjota Chicaiza, Ana Patricia (2020)
The general objective of this project is to develop a feasibility study for the creation of a micro enterprise dedicated to the production and commercialization of products made from chocho, located in the parish of San Buenaventura in the canton of Latacunga, province of Cotopaxi. The specific objectives proposed are: to determine the nature of the project through the description of the company and the products it offers; to investigate the supply and demand of the product through data obtained from primary and secondary sources; to define the size of the company according to the time, equipment and processes implemented in the project; to establish the human resources necessary for the company, as well as the fiscal and legal aspects to be considered; to analyze the feasibility of the business through the development of a financial study. The methodology used was a feasibility study provided by the Faculty of Administrative Sciences of the Technical University of Cotopaxi since it is the one that best suits the needs of the project. The market segmentation is based on the inhabitants over 20 years of age in the urban sector of the city of Latacunga, which is 46,142 people, where it was determined that 95.5% include chocho in their diet, establishing the existence of an annual demand of 142,678 kilograms. Once the technical study was carried out, the necessary resources were established for the implementation of the project and the optimal location of the production plant was determined. The size of the project will be 375,000 units of 32 grams in the first year. Finally, the financial and economic viability of the business was determined, starting with an investment of $50,250.35, 20.40% of which was contributed by shareholders, and the rest was financed by a loan requested from Ban Ecuador. The project confirms its feasibility since the NPV is greater than zero, the IRR was greater than the ARRM and the investment recovery period was 2 years and 3 months.